Bilateral investment treaties do work: Until they don't - Emma Aisbett; Matthias Busse; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2016)
The recent boom of investor-state disputes filed under international investment agreements has fueled a controversial academic and policy debate. Despite its importance, there has been very little work to date on the impacts of compensation claims by investors on FDI flows to the responding host country. We study this question using a comprehensive dataset of FDI flows, compensation claims and bilateral investment treaty (BIT) participation. We allow for differential impacts of compensation claims against a host on inward FDI flows from BIT-partner and non-partner countries. Focusing on these differences allows us both to shed new light on how investment treaties might influence investor behavior, as well as allowing us to control for unobserved changes in the host-country investment climate. We find that BITs stimulate bilateral FDI flows from partner countries - but only so long as the host country has not had a claim brought against it to arbitration. When a host faces a claim, FDI from sources with a BIT in place falls significantly more than that from unprotected sources. Furthermore, after the host has faced a claim, the entry into force of new BITs is no longer associated with increased FDI flows.
Keywords: F21; F23; F53; 330; bilateral investment treaties; investor-state dispute settlement; compensation claims; protected and unprotected investors